PKM TRAINING AND BUSINESS DEVELOPMENT AND DIGITAL MARKETING AT MSMES MITRA RAZZ FOOD SUPPLIER DEPOK WEST JAVA - Syahrudi, Syahrudi; Wahbi , Abdul Azim; Sahrudin, Sahrudin (Antis-publisher, 2024)
General background: MSMEs play a critical role in driving economic growth but often face challenges in financial management and digital marketing, hindering their competitiveness. Specific background: Razz Food Supplier Partner MSMEs, like many small enterprises, struggle with low digital literacy, which impacts their ability to manage finances and expand market reach effectively. Knowledge gap: Despite the increasing push towards digitalization, there is limited research on the practical application of computerized financial systems and digital marketing platforms in improving the operations of MSMEs, especially in the food supply sector. Aims: This community service project aims to enhance the financial management and digital marketing capabilities of Razz Food Supplier Partner MSMEs through the adoption of digital tools for bookkeeping and online marketing platforms. Results: The implementation of computerized financial systems significantly improved partners' financial reporting accuracy, minimized the mixing of personal and business funds, and enabled more precise profit calculations. Additionally, the use of digital marketing platforms expanded the market reach of MSMEs, enhancing their visibility and customer engagement. Novelty: This research uniquely integrates digital financial systems and marketing strategies tailored specifically to MSMEs in the food sector, providing practical solutions for overcoming the challenges of low digital literacy. Implications: The findings suggest that continued support for the digitalization of MSMEs can lead to substantial improvements in their operational efficiency, profitability, and market competitiveness. These insights contribute valuable recommendations for future community service programs aimed at fostering the long-term sustainability and growth of small businesses in the digital era.